Normative Gaps in the Protection of Education Rights of Persons with Intellectual Disabilities in the Inclusive Education System - Gesang Marchellino; Fahmi Ata Muttaqien; Aulia Akbar Mulyansyah; Galang Media Cakrawala; Aryatama Prasetiadi Nurdiansyah (Disable, 2025)
People with intellectual disabilities face the greatest systemic risk of educational rights violations, largely due to social stigma and weak legal protection. Under international human rights law, states are obligated to respect, protect, and guarantee these rights as outlined in the Convention on the Rights of Persons with Disabilities (CRPD). However, Indonesia’s domestic legislative framework does not adequately reflect these responsibilities. Research on the normative adequacy of legal protection in education for people with intellectual disabilities remains rare. This article addresses that gap through normative legal research and conceptual analysis, focusing on obligations of fulfillment and reasonable accommodation. The study examines Law No. 8 of 2016, Government Regulation No. 13 of 2020, Minister of Education and Culture Regulation No. 70 of 2009, and the CRPD. Findings highlight three concerns: the absence of specific protection norms, inconsistencies between international obligations and domestic regulations, and the lack of accessible repressive protection mechanisms. These shortcomings show Indonesia’s obligations are implemented only formally, without substantive effect. Therefore, regulatory reform is essential to achieve substantive equality and ensure the educational rights of individuals with intellectual disabilities, not as social policy but as a binding legal obligation.